Visual teaching strategies and Arabic language (Journal of the College of Basic Education, 2023)
The majority of modern linguists agree that the function of language is expression, communication, communication, or understanding. (Youssef, 1990, p. 27).Accordingly, expression is one of the important goals of language study and is a priority in learning it. (Al-Waqfi, 2009, p. 450).Despite its importance, it did not take its place within the curricula of the Arabic language and it constitutes linguistic practices in it, and the weakness of students in it and their inability to express seems to be a national problem and is evident in the thinness of their writings and their inability to understand the prescribed topics, and their presentation of weak and inconsistent arguments, and their expression in a language other than Accurate, and this weakness may be attributed to our educational system and its methods that focus on indoctrination and memorization, which are rarely exposed to the functional side of the crack in the life of the learner.And this was confirmed by Al-Hashemi, saying: